Beat-by-Beat Cardiomyocyte T-Tubule Deformation Drives Tubular Content Exchange. Issue 2 (22nd January 2021) - Rog-Zielinska, Eva A.; Scardigli, Marina; Peyronnet, Remi; Zgierski-Johnston, Callum M.; Greiner, Joachim; Madl, Josef; O'Toole, Eileen T.; Morphew, Mary; Hoenger, Andreas; Sacconi, Leonardo; Kohl, Peter
Abstract : Rationale: The sarcolemma of cardiomyocytes contains many proteins that are essential for electromechanical function in general, and excitation-contraction coupling in particular. The distribution of these proteins is nonuniform between the bulk sarcolemmal surface and membrane invaginations known as transverse tubules (TT). TT form an intricate network of fluid-filled conduits that support electromechanical synchronicity within cardiomyocytes. Although continuous with the extracellular space, the narrow lumen and the tortuous structure of TT can form domains of restricted diffusion. As a result of unequal ion fluxes across cell surface and TT membranes, limited diffusion may generate ion gradients within TT, especially deep within the TT network and at high pacing rates. Objective: We postulate that there may be an advective component to TT content exchange, wherein cyclic deformation of TT during diastolic stretch and systolic shortening serves to mix TT luminal content and assists equilibration with bulk extracellular fluid. Methods and Results: Using electron tomography, we explore the 3-dimensional nanostructure of TT in rabbit ventricular myocytes, preserved at different stages of the dynamic cycle of cell contraction and relaxation. We show that cellular deformation affects TT shape in a sarcomere length-dependent manner and on a beat-by-beat time-scale. Using fluorescence recovery after photobleaching microscopy, we show that apparent speed of diffusion is affected by the mechanical state of cardiomyocytes, and that cyclic contractile activity of cardiomyocytes accelerates TT diffusion dynamics. Conclusions: Our data confirm the existence of an advective component to TT content exchange. This points toward a novel mechanism of cardiac autoregulation, whereby the previously implied increased propensity for TT luminal concentration imbalances at high electrical stimulation rates would be countered by elevated advection-assisted diffusion at high mechanical beating rates. The relevance of this mechanism in health and during pathological remodeling (eg, cardiac hypertrophy or failure) forms an exciting target for further research. Abstract : Supplemental Digital Content is available in the text.